Geology of the Oil Fields of North Central Texas ? Discussion (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1918)
Discussion of the paper of DORSEY HAGER, to be presented at the Colorado meeting, September, 1918, and printed in Bulletin No. 138, June, 191S, pp. 1109 to 1118. WALLACE E. PRATT, Wichita Falls, Tex. (written discussion*).¬Mr. Hager has touched upon interesting problems related to the broad subject with which he has entitled his paper. As to the existence of the important structural feature in the buried Bend series, which Mr. Hager constructs from well-logs, and designates as the "Bend Arch," there seems to be general agreement among a number of observers. Indeed, M. G. Cheney1 and Robt. T. Hill2 have each published structural maps of the Bend Arch that do not differ essentially from the map shown in Mr. Hager's Fig. 1. The reflection, in the overlying, unconformable Cretaceous, of certain folds in the Pennsylvanian, with which the petroleum accumulations has to do, is an important observation on the part of Mr. Hager, since, as he says, much critical territory is covered by Cretaceous, and it is highly desirable that the underlying Pennsylvanian structure be mapped, if possible. If the folds in the Pennsylvanian are of post-Cretaceous age, then it should be possible, in spite of the intervening unconformity, to determine approximately the position of buried folds beneath the Cretaceous overlap. The idea of post-Cretaceous folding would not be out of accord with the suggestion by Carroll H. Wegemann that the folding of the Permian beds in southern Oklahoma was still in progress as late as the Tertiary.3 But most observers have related the folds in the Pennsylvanian and Permian beds at the surface, both in North Texas and southern Oklahoma, to the process of. emergence of the land area at the end of the Permian. It seems more probable that the reflection of Pennsylvanian folds in the unconformable Cretaceous which Mr. Hager observed is due to long continued persistence of stresses which were largely relieved at the close of the Permian, than that the principal period of folding was post-Cre-taceous; this being the case, it seems likely that only folds of greatest intensity in the Pennsylvanian will, be decipherable in the Cretaceous overburden, and that many promising structural features are so concealed by the Cretaceous as to escape detection except by drilling.